A Systematic Review and Meta-Analysis Comparing Carer Focused and Dyadic Multicomponent Interventions for Carers of People With Dementia. (December 2017) - Laver, Kate; Milte, Rachel; Dyer, Suzanne; Crotty, Maria
Objective: The aim of this study was to compare the efficacy of two approaches: multicomponent interventions that focus on working with the carer and dyadic interventions that work with both the carer and the person with dementia.Method: A systematic review involving a search of Medline, EMBASE, and PsycINFO in October 2015 was performed. Randomized controlled trials involving carers of people with dementia and comparing multicomponent interventions with usual care were included.Results: Pooling of all studies demonstrated that multicomponent interventions can reduce depressive symptoms, improve quality of life, reduce carer impact, and reduce behavioral and psychological symptoms of dementia as well as caregiver upset with these symptoms. We were unable to find a significant difference in the effects of dyadic interventions in comparison with carer focused interventions for these outcomes.Discussion: Although effect sizes associated with intervention are small, multicomponent interventions are relatively inexpensive to deliver, acceptable, and widely applicable.